RESIDUAL PHENOMENA OF THE TRANSFERRED COVID-19 IN THE MAXILLOFACIAL REGION OR ITS COMPLICATIONS - O.V. Rybalov; M.G. Skikevych; O.Yu. Andriyanova; P.I. Yatsenko (Український стоматологічний альманах, 2021)
Today, the issues of the incidence of the Covid-19 virus and its complications are extremely relevant. Much attention in the scientific literature is paid to possible complications such as sufferings of the lungs, heart. Along with this, it became known that the coronavirus can affect the brain, nasopharynx, eyes, blood vessels, liver, kidneys and intestines. Interesting data from clinicians and morphologists has been received. Those who have had Covid-19 note the long-term effects of scarring of the lung tissue and kidney failure, inflammation of the heart muscle, arrhythmias, liver damage, cognitive impairment, psychosis, accompanied by a sharp change in mood. Interesting observations from the Department of Systems Biology at George Mason University were seen: 70% of patients who have had Covid-19 rarely observe pathology of internal organs.